Controlled morphologies by molecular design and nano-imprint lithography - Pfadler, Thomas; Palumbiny, Claudia M.; Pisula, Wojciech; Hesse, Holger C.; Feng, Xinliang; Muellen, Klaus; Mueller-Buschbaum, Peter; Schmidt-Mende, Lukas (Springer New York LLC, 2017)
In this review we report on the recent advances concerning molecular design and nano-imprint techniques to improve the morphology of organic solar cells. Advanced scattering techniques allow us to resolve issues pertaining to the alignment and crystallization of the photoactive materials of nanostructured solar cells. Interfacial design at a donor–acceptor heterojunction is one of the key issues for improved device performance.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Advanced scattering techniques; Discotic molecules; Molecularassembly; Nanoimprint lithography